Associations of LIG4 and HSPB1 Genetic Polymorphisms with Risk of Radiation-Induced Lung Injury in Lung Cancer Patients Treated with Radiotherapy. (25th February 2015) - Xu, Feng; Han, Ji-Chang; Zhang, Ya-Jun; Zhang, Yi-Jie; Liu, Xiao-Chun; Qi, Guan-Bin; Liu, Dan; Chen, Yan-Zhi; Zhao, Yu-Xia; Bai, Lu
Abstract : Objective. This study aims to explore the correlations of genetic polymorphisms in LIG4 and HSPB1 genes with the radiation-induced lung injury (RILI), especially radiation pneumonitis (RP), in lung cancer patients. Methods. A total of 160 lung cancer patients, who were diagnosed with inoperable lung cancer and received radiotherapy, were included in the present study from September 2009 to December 2011. TaqMan Real-Time PCR (RT-PCR) was used to verify the SNPs of LIG4 and HSPB1 genes. Chi-square criterion was used to compare the differences in demographic characteristics, exposure to risk factors, and SNPs genotypes. Crude odds ratios (ORs) with 95% confidence intervals (95% CI) were calculated by logistic regression analysis. All statistical analyses were conducted in SPSS 18.0. Results. A total of 32 (20.0%) lung cancer patients had RP after receiving radiotherapy. Of the 32 cases, 4 cases were of grade 2, 24 cases were of grade 3, and 4 cases were of grade 4. However, our results indicated that the general condition and treatment of all patients had no significant difference with RP risk ( P > 0.0 5 ) . Meanwhile, our results revealed that there was no significant association between the frequencies of LIG4 rs1805388 and HSPB1 rs2868371 genotype distribution and the risk of RP ( P > 0.05 ) . Conclusion. In conclusion, we demonstrated that the genetic polymorphisms in LIG4 rs1805388 and HSPB1 rs2868371 were not obviously correlated with the risk of RP and RILI of lung cancer.